Intelligent Systems for Demand Forecasting and Production Planning - Hrama, Mykhailo (My University, 2025)
In today’s competitive and rapidly changing market environment, accurate demand forecasting and efficient production planning have become critical factors for the success of manufacturing and food industry enterprises. Traditional planning methods, which often rely on historical averages and manual adjustments, struggle to keep pace with fluctuating consumer preferences, seasonal variations, and dynamic supply chain conditions. Intelligent systems that integrate machine learning, artificial intelligence, and advanced analytics offer a transformative approach, enabling companies to make data-driven decisions, optimize resource allocation, and minimize waste while ensuring timely delivery of products. У сучасному конкурентному та швидкозмінному ринковому середовищі точне прогнозування попиту та ефективне планування виробництва стали критично важливими факторами успіху підприємств виробничої та харчової промисловості. Традиційні методи планування, які часто спираються на історичні середні значення та ручне коригування, навряд чи встигають за змінами вподобань споживачів, сезонними коливаннями та динамічними умовами ланцюга поставок. Інтелектуальні системи, що інтегрують машинне навчання, штучний інтелект та передову аналітику, пропонують трансформаційний підхід, що дозволяє компаніям приймати рішення на основі даних, оптимізувати розподіл ресурсів та мінімізувати втрати, забезпечуючи своєчасну доставку продукції.
Keywords: machine learning; big data; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки; машинне навчання; великі дані